Università Oggi: polarità, scarti e problematicità - Riva, Maria Grazia (Studi sulla Formazione/Open Journal of Education, 2019)
<span style="font-family: Arial,sans-serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-origin: initial; background-clip: initial;" lang="EN-GB">Universities are in a condition which, from certain points of view, is paradoxical. On the one hand, scientific research is increasingly advanced and at the scientific and technological cutting-edge. On the other hand, the progress of scientific research has definitely not led to the well-being of society. It is impossible not to wonder what relationship there is between the advance of knowledge and the repercussions on society. There is a wide chasm which raises serious questions on the detachment between the places where knowledge is constructed and society as a whole. A balance has to be found between the appropriate respect for the tasks of teaching, research, spreading knowledge and the need to regain the depth and critical and reflective substance intrinsic in handing on the baton from one generation to the next